2006
DOI: 10.1016/j.enbuild.2005.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison groups on bills: Automated, personalized energy information

Abstract: A program called "Innovative Billing" has been developed to provide individualized energy information for a mass audience-the entire residential customer base of an electric or gas utility. Customers receive a graph on the bill that compares that customer's consumption with other similar customers for the same month. The program aims to stimulate customers to make efficiency improvements. To group as many as several million customers into small "comparison groups", an automated method must be developed drawing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 5 publications
1
16
1
Order By: Relevance
“…Asked directly, most survey respondents said they understood their PowerChoice bill and found it useful. 61 Ontario's study on residential pilot TOU found that participants said that their monthly usage statements were very useful in adjusting to the TOU rates (Ontario Energy Board 2007), confirming other studies suggesting that bills are potentially a very important tool for customer learning (Iyer et al 2006;Wilhite & Ling 1995). 60.…”
Section: Reading and Critiquing The Billssupporting
confidence: 56%
See 1 more Smart Citation
“…Asked directly, most survey respondents said they understood their PowerChoice bill and found it useful. 61 Ontario's study on residential pilot TOU found that participants said that their monthly usage statements were very useful in adjusting to the TOU rates (Ontario Energy Board 2007), confirming other studies suggesting that bills are potentially a very important tool for customer learning (Iyer et al 2006;Wilhite & Ling 1995). 60.…”
Section: Reading and Critiquing The Billssupporting
confidence: 56%
“…Bill design matters. Several studies have documented the importance of bill design as a means of feedback (Iyer et al 2006;Wilhite & Ling 1995). While a monthly bill can provide only retrospective and crude information relative to the intricacy of electricity use, a user-friendly, information-rich bill design may encourage goodwill and more exacting Time-of-Use response from participants.…”
Section: Recommendations For Residential Tou Programsmentioning
confidence: 99%
“…In general, Egan and colleagues [43] found that the comprehension of the graphics was relatively low, but that adding end-point labels to the charts helped. In marked contrast to these findings are those of Iyer and colleagues [50] who found that the distribution chart was easily understood by participants. In another study, Wilhite and colleagues [48] found their focus group participants were divided over the preference for linear representation and distribution charts for depicting energy consumption.…”
Section: Presentation Of Energy Consumption Detailcontrasting
confidence: 51%
“…Indeed, the effect of peers has been found to be more effective than incentives such as saving money, conserving resources, or being socially conscious [51]. Whilst the highest quality comparison combines various household attributes it has also been suggested that for practicality, individual streets in groups of 30 addresses is a good basis for geographical comparison [50]. An additional benefit of this type of comparative feedback is that there is no need for weather-adjusting.…”
Section: Normative Standardsmentioning
confidence: 99%
“…Other authors have emphasized the importance of social processes (Homans [36]; Garmendia and Stagl [37] and formation of sustainable behavior in communities (Nunes [38]). Also a significant part of the study was to reveal the information and different types feedback influence on energy savings behavior (Roberts and Baker [39]; Ueno [40]; Darby [41]; Iyer et al [42]). Another important research unit includes environmental behavior shaping ethical, cultural, worldview and human capital issues (Wallerand et al [43]; Bamberg and Schmidt [44]; Barnet and Serletis [45]).…”
Section: Introductionmentioning
confidence: 99%